Propuesta de etiquetaje pragmático para un corpus conversacional en español - Khaylina, Anastasia; Alvarado Ortega, M. Belén (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper proposes a system of pragmatic tagging for the VALESCO.HUMOR corpus, available at the Observahumor.com website. To date, the work of the GRIALE group has involved the study of irony and humour in Spanish, leading to the creation of a taxonomy of humour markers and indicators that serve to identify ironic and humorous utterances in the corpus. Markers are elements that help in the interpretation of an utterance as humorous (e.g., intonation or laughter), whereas indicators are humorous elements per se (e.g., certain suffixes or phraseological units). Timofeeva and Ruiz Gurillo (2021) have developed a pilot version of a pragmatic tagging system, based on markers and indicators, for the CHILDHUM corpus (also available at Observahumor.com). However, their system incorporates characteristics which are applicable to that specific corpus of children’s narratives, and as such cannot easily be extrapolated to all the corpora hosted at Observahumor.com. For this reason, it is necessary to carry out a detailed study of the pragmatic tags that might best be used towards a better interpretation of each text therein, and hence that would be suitable for each type of corpus. In the present study we present a proposal for the VALESCO.HUMOR corpus, which comprises 148 ironichumorous sequences extracted from 67 colloquial conversations of the Val.Es.Co. corpus (http://www.valesco.es/). The aim of this proposal is to provide the reader with all the necessary information to be able to interpret these humorous sequences and thus be able to analyse the corpus adequately..